Phenotypic plasticity in cell walls of maize brown midrib mutants is limited by lignin composition - Vermerris, Wilfred (Oxford University Press, 2010)
The hydrophobic cell wall polymer lignin is deposited in specialized cells to make them impermeable to water and prevent cell collapse as negative pressure or gravitational force is exerted. The variation in lignin subunit composition that exists among different species, and among different tissues within the same species suggests that lignin subunit composition varies depending on its precise function. In order to gain a better understanding of the relationship between lignin subunit composition and the physico-chemical properties of lignified tissues, detailed analyses were performed of near-isogenic brown midrib2 (bm2), bm4, bm2-bm4, and bm1-bm2-bm4 mutants of maize. This investigation was motivated by the fact that the bm2-bm4 double mutant is substantially shorter, displays drought symptoms even when well watered, and will often not develop reproductive organs, whereas the phenotypes of the individual bm single mutants and double mutant combinations other than bm2-bm4 are only subtly different from the wild-type control. Detailed cell wall compositional analyses revealed midrib-specific reductions in Klason lignin content in the bm2, bm4, and bm2-bm4 mutants relative to the wild-type control, with reductions in both guaiacyl (G)- and syringyl (S)-residues. The cellulose content was not different, but the reduction in lignin content was compensated by an increase in hemicellulosic polysaccharides. Linear discriminant analysis performed on the compositional data indicated that the bm2 and bm4 mutations act independently of each other on common cell wall biosynthetic steps. After quantitative analysis of scanning electron micrographs of midrib sections, the variation in chemical composition of the cell walls was shown to be correlated with the thickness of the sclerenchyma cell walls, but not with xylem vessel surface area. The bm2-bm4 double mutant represents the limit of phenotypic plasticity in cell wall composition, as the bm1-bm2-bm4 and bm2-bm3-bm4 mutants did not develop into mature plants, unlike the triple mutants bm1-bm2-bm3 and bm1-bm3-bm4.